A Phase 1 study of BAL101553, a novel tumor checkpoint controller targeting microtubules, administered as 48-h infusion in adult patients with advanced solid tumors - Joerger, Markus (Invest New Drugs, 2019)
Purpose BAL101553, the prodrug of the microtubule-destabilizer BAL27862, previously showed signs of antitumor activity when administered as a 2-h infusion, but its use was limited by vascular toxicity. We investigated an alternative dosing strategy aimed at improving the safety profile of BAL101553. Methods This multicenter, open-label, Phase 1 dose-escalation study used a 3 + 3 design to determine the maximum tolerated dose (MTD), dose-limiting toxicities (DLTs), pharmacokinetics, and antitumor activity of BAL101553 administered as a 48-h IV infusion on Days 1, 8, and 15 of a 28-day cycle. Patients received oral BAL101553 on Days 15–21 of cycle 2 to assess oral bioavailability. Results BAL101553 was well tolerated at doses up to ≤70 mg/m(2). Three grade 3 DLTs occurred: hypotension (70 mg/m(2)), hyponatremia and neutropenia (both 90 mg/m(2)). The MTD for 48-h IV BAL101553 was 70 mg/m(2). At this dose level, the AUC for BAL27862 was 8580 ng.h/mL and the C(max) was 144 ng/mL. No apparent dose-related effects on blood pressure were observed with 48-h BAL101553 IV infusion. BAL27862 oral bioavailability was >80%. Conclusions Continuous 48-h IV BAL101553 infusion achieved higher exposure of the BAL27862 active metabolite than a 2-h infusion at the RP2D and did not cause vascular toxicity. Clinicaltrials.gov registration: NCT02895360. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10637-019-00850-z) contains supplementary material, which is available to authorized users.